Diffusion tensor imaging and voxel-based morphometry reveal corticospinal tract involvement in the motor dysfunction of adult-onset myotonic dystrophy type 1. Issue 1 (December 2018) - Park, Jin-Sung; Song, Huijin; Jang, Kyung; Cha, Hyunsil; Lee, Sang-Hoon; Hwang, Su-Keong; Park, Donghwi; Lee, Hui; Kim, Jun-Young; Chang, Yongmin
Abstract Magnetic resonance imaging (MRI) studies have demonstrated that patients with myotonic dystrophy type 1 (DM1) exhibit gray and white matter abnormalities that are correlated with various genetic and neuropsychological measures. However, few MRI studies have focused on the correlations between brain abnormalities and overall motor function including gait performance. Here, we investigated the correlations between brain abnormalities, as assessed with MRI including diffusion tensor imaging (DTI), and motor performance, as assessed with the Medical Research Council sum score (MRCSS), 6-minute walk test (6MWT), and hand grip power, in patients with DM1. Eighteen patients with DM1 and twenty healthy controls participated in this study. The MRCSS and 6MWT reflect patients' general motor performance, particularly gait, while hand grip reflects the presence of myotonia. We found significant relationships between DTI parameters in the corticospinal tract (CST) and genetic factors and motor performance in patients with DM1. These findings suggest that CST involvement reflecting deterioration of the motor tracts may play a significant role in clinical myotonia. Further, a direct relationship between the cortical gray matter volume and DTI measures in the CST suggests that white matter abnormalities in the CST are strongly associated with volume reductions in the sensorimotor cortex of patients with DM1.